Teachers’ Beliefs and Practice in the Linguistics Classroom - Ghaouar, Nesrine (Journal of History Culture and Art Research, 2015)
Teachers’ Beliefs and Practice in the Linguistics Classroom Abstract Teaching refers to all the activities that are intended to bring about language learning. Teaching does not only include teacher’s skills and knowledge, rather it includes even their beliefs. It has been argued that teachers’ beliefs are stronger that their knowledge. Teachers’ beliefs include their beliefs about their learners, learning and about themselves as persons. But do teachers preach what they teach? in order words, “ Do teachers’ practice what they believe in?” and “ Is there a discrepancy between what teachers do and what they think they do in their classrooms? A study has been conducted with teachers of first year linguistics in the department of English-Badji Mokhtar University- Annaba. First year linguistics aims at developing learners’ background knowledge and awareness of certain terminology related to this field of study. The questionnaire revealed that for the majority of teachers what they believe in is not reflected in how they teach.